Influence of buffer composition and sample pretreatment on efficiency separation for monitoring neuropeptides in plasma using capillary electrophoresis - Ban, E; Choi, OK; Chung, WY; Park, CS; Yoo, EA; Chung, BC; Yoo, YS (WILEY-V C H VERLAG GMBH, 2001)
More efficient and faster separation, conditions for qualitative as well as quantitative analysis of neuropeptides in human plasma using capillary zone electrophoresis (CZE) have been developed. The analysis method for neuropeptides has been improved specifically to study thyroid hormone related neuropetides for the regulation of thyroid disease. In this study, we investigated the pretreatment methods, composition of the running buffer and rinsing procedures between runs in order to obtain more sensitive and faster separation of trace neuropeptides in plasma by CZE. The tested neuropeptides were somatostatin (SOMA), vasopressin (VP), neurotensin (NT), and thyrotropin-releasing hormone (TRH). Plasma samples were pretreated by deproteinization and solid-phase extraction method. The fraction of neuropeptides was reconstituted in 40% acetonitrile followed by ultrafiltration, and then analyzed by CZE. Resolution and sensitivity was improved using the separation buffer composition with 100 mM Tris-phosphate buffer (pH 2.0) while the sensitivity was further improved via a stacking method using the sample buffer of 40% acetonitrile. These sample pretreatment methods and buffer condition permit quantitative analysis on tested neuropeptides at the 20 ng/mL level. The rinsing procedures between runs using 90% ethanol dramatically shortened the rinsing time to 30 min.
Keywords: ZONE-ELECTROPHORESIS; CHROMATOGRAPHY; PEPTIDES; STACKING; PROTEIN; ACID